Conventional Echocardiography and Two-Dimensional Speckle Tracking in Healthy Sevoflurane-Anesthetized Dogs Undergoing Continuous Rate Infusion of Nalbuphine - Marques, Marcel G. [UNESP]; Marques, Ana Elisa G. W. [UNESP]; De Siqueira, Carlos E. [UNESP]; De Sousa, Élen A. P. [UNESP]; Ribeiro, Yan S. [UNESP]; Floriano, Beatriz P.; Ferreira, Wagner L. [UNESP]; Santos, Paulo S. P. [UNESP] (Hindawi, 2020)
Nalbuphine is an agonist-antagonist opioid with adequate analgesic properties and few depressant effects on the respiratory system. However, there are no detailed reports available on cardiovascular effects of nalbuphine in dogs. The aim of this study was to assess the effects of a continuous rate infusion (CRI) of nalbuphine on left ventricular systolic and diastolic function of healthy sevoflurane-anesthetized dogs. Eighteen mixed-breed bitches aged 1-4 years and weighing 9.9 ± 3.8 kg were used. Dogs were randomly assigned to one of two groups: nalbuphine (GN, n = 9) and control (GC, n = 9). Anesthesia was induced and maintained with sevoflurane (2V%) followed by an intravenous (IV) bolus of nalbuphine (0.3 mg/kg) or 0.9% NaCl at equal volume and then CRI of nalbuphine (0.4 mg/kg/h) or 0.9% NaCl at an equal infusion rate. Echocardiographic and hemodynamic variables were determined at baseline and 20, 40, 60, and 80 minutes following start of CRI. No differences were found between groups for left ventricular systolic and diastolic variables obtained through conventional echocardiography and two-dimensional speckle tracking. Likewise, hemodynamic variables did not differ between groups. The E′/A′ ratio significantly increased at 20 minutes compared to baseline only in GN. Nalbuphine given at a CRI does not influence left ventricular systolic and diastolic function in healthy sevoflurane-anesthetized dogs.